Determination of the uptake and utilization of nitrogen in Curcuma alismatifolia Gagnep. using15N isotope - Soraya Ruamrungsri (2018)
Rhizomes of Curcuma alismatifolia Gagnep. were planted in a soil-less culture medium composed of sand: perlite mixed at a ratio of 1:1. Three groups of plants were fed with a15N ( 40 mg N L-1+ 10 mg N L-1)-labeled culture solution over three different periods: (1) Period 1: from root emergence (2 weeks after planting [WAP]) to the two expanded leaf stage (Stage 1: 6 WAP), (2) Period 2: from Stage 1 to the first floret opening stage (Stage 2: 9 WAP), (3) Period 3: from Stage 2 to harvest during dormancy (Stage 3: 24 WAP). Plants received the same composition of non-labeled N from 2 WAP to 24 WAP, except for the15N-labeling period. The fourth group of plants was cultured in a nitrogen-free solution and the fifth group was cultured in a complete solution (referred to as control treatment) from planting until harvest and sampled to determine the changes in total N content. Nitrogen content and15N abundance were determined at different stages of growth. Average absorption of15N from the culture solution was 23.5 mg N plant-1during Period 1, 97.8 mg N plant-1during Period 2 and 78.7 mg N plant-1during Period 3. Daily N absorption rates per plant were 0.84 mg N during Period 1, 4.66 mg N during Period 2 and 0.75 mg N during Period 3. A large amount of absorbed nitrogen was translocated to the compact spike, particularly in Period 2. At harvest the nitrogen accumulation was partitioned almost equally between new rhizomes and storage roots. Most of the absorbed nitrogen in the new rhizomes and storage roots was derived from that received during Period 3. © 2006 Japanese Society of Soil Science and Plant Nutrition.